Keseimbangan Sitokin Th1/Th2 Berperan Dalam Proliferasi Mastosit Jaringan Paru Pasca Pemberian Diet Tinggi Lemak pada Tikus - Rosita, Rita; Indra, Muhamad Rasjad; Widjajanto, Edi (Jurnal Kedokteran Brawijaya, 2009)
ABSTRACTAsthma and obesity are prevalent disorders, each with a significant public health impact, and a large andgrowing body of literature suggests an association between the two. The systemic inflammatory milieu inobesity leads to metabolic and cardiovascular complications but this environment alters asthma risk orphenotype is not yet known. Studies that evaluated the effects of leptin and obesity on airway inflammationin response suggest that air way inflammation is enhanced by leptin. Leptin is stimulate a Th1 cytokineprofile and suppresses Th2 cytokine production. Whether resistance to the effects of the lung or on immunefunction is unknown, but such resistance might be expected to polarize to a Th2. The aim of this study isidentify effect of leptin to lung mast cell proliferation via shifting Th1/Th2 balance using diet-induced obesemice. Because there are contradictive between leptin immune function in leptin deficient and obese, tounderstand the effect of leptin in diet-induced obese mice on immune function, lung mast cell proliferationand correlation with IL-4 as represent cytokine Th2 and IL-2 represent cytokine Th1 has been studied.